1987
DOI: 10.1007/bf01486966
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of psychiatric illness in children with early speech/language problems

Abstract: This paper reports on the correlates of psychiatric illness in children with speech and language disorders. Of 600 children selected from a community speech clinic, 50% were found to have diagnosable psychiatric disorders according to DSM-III criteria. These "psychiatrically ill" children were compared to the "psychiatrically well" children in the sample on a variety of developmental, socioeconomic, medical, and psychosocial factors. Although some differences were found between the well and ill children in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…This may be due to differences in the participants selected. For example, Stevenson and Richman (1978) selected younger children than those in the present study; and Baker and Cantwell (1987) selected a wider age range, but with a younger mean age of 5 years and 7 months. This suggests that children with language disorders may grow out of associated emotional difficulties as they get older.…”
Section: Anxiety In H Igh F Unctioning Children With Autismmentioning
confidence: 98%
See 3 more Smart Citations
“…This may be due to differences in the participants selected. For example, Stevenson and Richman (1978) selected younger children than those in the present study; and Baker and Cantwell (1987) selected a wider age range, but with a younger mean age of 5 years and 7 months. This suggests that children with language disorders may grow out of associated emotional difficulties as they get older.…”
Section: Anxiety In H Igh F Unctioning Children With Autismmentioning
confidence: 98%
“…Speech and language disorders have been found to be associated with high rates of psychiatric disturbance, particularly in childhood (Baker & Cantwell, 1987;Beitchman et al, 1996). An epidemiological study by Stevenson and Richman (1978) found that children with a delay in expressive language displayed significantly more behaviour problems than children with normal language development.…”
Section: Comparison Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nelson and colleagues reported that the language deficits of students with ED were stable across age (Nelson, Benner, & Cheney, 2005). Because successful language acquisition is a prerequisite for successful academic learning in all areas (Baker & Cantwell, 1987;Catts, Fey, Xuyang, & Tomblin, 1999), the language deficits of students with ED are likely to have a negative influence on their academic achievement.…”
mentioning
confidence: 99%